The role of organizational communication in the trust-building process in the organization (on the example of the RA labor market) - Gevorgyan, Anahit (Bulletin of Yerevan University E: Philosophy, Psychology, 2025)
In today’s fast-changing labor market, creating an atmosphere of trust within an organization is crucial for its stability and success. Trust serves as a foundation in the relationship between employees and the organization, gaining even more importance during times of crisis. Examining the role of organizational communication and other influential factors in building trust will enable HR professionals and leadership teams to direct resources to ensure a high level of trust within the organization. This is especially important in the rapidly changing environment, where ensuring high organizational performance and employee engagement are among organizations’ key challenges. This research aims to study the role of organizational communication in the process of building trust in the organization, as well as to identify the key factors that influence trust formation. It is assumed that in organizations where employees rate the quality of communication high, trust in the organization is also at a higher level. The survey method was used to conduct the research. According to the research results, there is a positive correlation between trust in the organization and the level of communication within the organization (r=0.72). In the process of employees’ trust in the organization, the most important factors are leadership honesty, a healthy and positive work environment, transparency, and leadership support.